The effects of reciprocal, self–check, and command teaching styles on dance learning - Durdica Miletic; Alen Miletic; Slavoljub Uzunovic (Physical Education of Students)
Background and Study Aim. Implementation of dance in physical education is in conformity with the requirements of modern education which fosters lifelong exercise for health and quality of life. The study aimed to determine which of the applied teaching styles would have the most significant impact on dance learning and the improvement of dance performance. Additionally, to assess the effects of these teaching styles on factors such as Task climate, Social relatedness, Autonomy, and Ego climate, as well as the relationship between these effects and gender.